Побудови області збіжності перетворення Ейлера степеневого ряду аналітичної функції - Сухорольський, М.; Микитюк, О.; Коломієць, В. (Видавництво Національного університету "Львівська політехніка", 2006)
Досліджено область збіжності перетворення Ейлера збіжного в одиничному крузі степеневого ряду аналітичної функції. Показано, що перетворення продовжує ряд за межу його круга збіжності за умови скінченної кількості особливих точок функції або одностороннього розташування щодо координатних осей особливих точок. The domain of convergence of Euler's transformation, convergent in the single circle of the power series of the analytical function is investigated in the paper. It is shown that the transformation continues a series beyond the boundary of the circle of convergence on condition that the number of the singular points of the function is finite and they are unilateral relative to their coordinate axes. In particular, it is shown that the series of the function singular points of which are located on the beam is summarized by the transformation in the half-plane.
On the constraction of convergence domain of Euler’s transformation of power series of analytical function
Keywords: перетворення Ейлера; степеневий ряд; аналітична функція; Euler's transformation; power series; analytical function